2016
DOI: 10.1080/15438627.2016.1258640
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stretching on the performance and injury risk of long-distance runners

Abstract: Stretching, either prior to exercise or at the end, or both, is typically carried out by all individuals undertaking sporting activity whether they be elite or recreational athletes. The many forms of stretching available to the athlete, either passive or active, have long been thought to improve performance, decrease injury and generally be advantageous to the athlete. This review examines the current state of the literature and evaluates what athletes can and should do with respect to this controversial topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 57 publications
1
37
0
4
Order By: Relevance
“…In amateur marathoners, XX runners have higher muscle flexibility than RX runners and have higher ankle dorsiflexion values than RR runners [15]. Although it has been suggested that muscle flexibility neither improve nor decrease the likeliness of developing running-related injuries [31], extreme cases outside the normal range of flexibility might predispose to endurance running injuries. Taken together, this information might be indicative of a higher likelihood of suffering any type of endurance running injury in R-allele carriers, especially RR runners.…”
Section: Discussionmentioning
confidence: 99%
“…In amateur marathoners, XX runners have higher muscle flexibility than RX runners and have higher ankle dorsiflexion values than RR runners [15]. Although it has been suggested that muscle flexibility neither improve nor decrease the likeliness of developing running-related injuries [31], extreme cases outside the normal range of flexibility might predispose to endurance running injuries. Taken together, this information might be indicative of a higher likelihood of suffering any type of endurance running injury in R-allele carriers, especially RR runners.…”
Section: Discussionmentioning
confidence: 99%
“…Stretching and core stability exercises were used by a high proportion of runners (86.2% and 70.2% respectively) despite a lack of evidence showing these strategies are effective at reducing injury risk (3,18,21,33), enhancing recovery (3) and improving performance (3,42).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence is contradictory regarding the assumption that better muscle flexibility, especially in the lower extremities, reduces the risk of injury in endurance runners [168]. Muscle flexibility was suggested to neither improve nor decrease likelihood of endurance running injuries, although extreme cases outside the normal range of flexibility might be problematic because of interference with the normal pattern of running [169]. In addition, the use of chronic stretching is effective to increase muscle flexibility but might negatively impact endurance running economy [20]; therefore, stretching could be performed to allow normal range of mobility during running.…”
Section: Factors Associated With Running-related Injuriesmentioning
confidence: 99%